2022
DOI: 10.1021/acsami.1c25087
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Effects of Zr Substitution and Carbon Additive on Li3–xEr1–xZrxCl6 Halide Solid Electrolytes

Abstract: Halide solid electrolytes have been considered as the most promising candidates for practical high-voltage all-solidstate lithium-ion batteries (ASSLIBs) due to their moderate ionic conductivity and good interfacial compatibility with oxide cathode materials. Aliovalent ion doping is an effective strategy to increase the ionic conductivity of halide electrolytes. However, the effects of ion doping on the electrochemical stability window of halide electrolytes and carbon additive on electrochemical performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 48 publications
2
51
1
Order By: Relevance
“…For instance, Shao et al used a mechanochemical method to synthesize a series of Zr-doped Li 3−x Er 1−x Zr x Cl 6 HSSEs and systematically investigated the impact of Zr doping on the ECW. [151] A CV measurement performed on the LiIn/ LPSCl/HSSE/HSSE + VGCF cell to evaluate the Zr doping impact on the ECW of Li 3−x Er 1−x Zr x Cl 6 (Figure 11b-i). The Er 3+ ion begins to be reduced at 0.85 V and the oxidation potential of Li 3 ErCl 6 is 4.26 V (Figure 11b,c), showing a broad ECW of 0.85-4.26 V. After Zr doping of Li 3 ErCl 6 in the form of Li 2.6 Er 0.6 Zr 0.4 Cl 6 , the oxidation stability is reduced to 4.21 V while its reduction potential increased to 1.67 V (Figure 11d,e).…”
Section: Experimental Intrinsic Electrochemical Stabilitymentioning
confidence: 99%
“…For instance, Shao et al used a mechanochemical method to synthesize a series of Zr-doped Li 3−x Er 1−x Zr x Cl 6 HSSEs and systematically investigated the impact of Zr doping on the ECW. [151] A CV measurement performed on the LiIn/ LPSCl/HSSE/HSSE + VGCF cell to evaluate the Zr doping impact on the ECW of Li 3−x Er 1−x Zr x Cl 6 (Figure 11b-i). The Er 3+ ion begins to be reduced at 0.85 V and the oxidation potential of Li 3 ErCl 6 is 4.26 V (Figure 11b,c), showing a broad ECW of 0.85-4.26 V. After Zr doping of Li 3 ErCl 6 in the form of Li 2.6 Er 0.6 Zr 0.4 Cl 6 , the oxidation stability is reduced to 4.21 V while its reduction potential increased to 1.67 V (Figure 11d,e).…”
Section: Experimental Intrinsic Electrochemical Stabilitymentioning
confidence: 99%
“…The Zr(IV) replaces the M(III), and the excess charge is compensated by a lithium vacancy. In all cases, the ionic conductivity measured by impedance spectroscopy has been shown to increase up to a certain substituent concentration [18][19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 95%
“…For the chloride Li3M(III)Cl6, this was successfully achieved by Zr(IV) substitution for M(III) = Y (ref. 19 ), Er (ref 19,20 ), Yb (ref. [21][22][23] ), In (ref.…”
Section: Introductionmentioning
confidence: 99%
“…In a rare example, Pan et al systematically investigated the effect of Zr doping on the electrochemical stability of Li 3 ErCl 6 . 23 It was found that although Zr doping improved the ionic conductivity, the higher reduction potential of Zr 4+ compared to In 3+ resulted in a reduced Li 3 ErCl 6 electrochemical stability window. However, no studies on the electrochemical stability of Li 3 InCl 6 , a very important member of the halide SE family, have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, previous aliovalent substitution research has frequently overlooked electrochemical stability. In a rare example, Pan et al systematically investigated the effect of Zr doping on the electrochemical stability of Li 3 ErCl 6 . It was found that although Zr doping improved the ionic conductivity, the higher reduction potential of Zr 4+ compared to In 3+ resulted in a reduced Li 3 ErCl 6 electrochemical stability window.…”
Section: Introductionmentioning
confidence: 99%